Criminological Study of Traffic Violations on Numbing Island - Widiyani, Heni; Purnomo, Armando Tri Cahyo; Marlina, Marlina; Efritadewi, Ayu; Susanti, Heni (JURNAL MERCATORIA, 2024)
Traffic violations are no longer commonplace among society. This often happens in the community, sometimes even causing economic and physical losses due to traffic accidents. Positive law in Indonesia has explicitly regulated traffic safety rules which are regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation. To study this, researchers took the research location Numbing Island, which is one of the islands in the Riau Islands Province. And from a criminological perspective, researchers want to examine in more depth what is the basis for the perpetrator to commit this offense. The research method used is empirical juridical research. As support in building the arguments for this research, researchers used primary and secondary reference materials. Data collection techniques used by researchers include observation methods, interviews and literature review. The research data analysis technique was carried out using a qualitative method, then in developing a line of thinking, the researcher used a deductive method. The results of this research show that the level of traffic violations on Numbing Island is sociologically caused by a lack of public awareness on the grounds that the application of traffic laws in the island area is not necessary, in terms of law enforcement factors, supervision by Bhabinkamtibmas is still not strictly implemented so that there is a form of negligence on the part of the authorities. law enforcers to enforce traffic regulations.